Thinking on the purposes, roles and activities of networks for research on maternal and perinatal health: opinions of coordinators and members - Vilma Zotareli; Silvana Bento; Renato Souza; José Guilherme Cecatti (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2024)
Abstract Objective To identify the opinion of coordinators and members about the essential characteristics and to understand the research networks characteristics, to facilitate their implementation, sustainability and effectiveness so it can be replicated in low and middle-income countries. Methods A qualitative study using a semi-structured interview technique was conducted. We selected potential members, managers and participants of networks from publications identified in PubMed. After checking the FIGO congress program, we identified authors who were assigned as speakers at the event. An invitation was sent and interviews were scheduled. Results In total, eleven interviews were performed. Coordinators and members of networks have the same goal when they decide to participate in a network. In general, they cited that these individuals had to be committed, responsible and enthusiastic people. The network should be composed also of postgraduate students. A network should allow multi-leadership, co-responsibility, autonomy and empowerment of its members. Effective communication was mentioned as an important pillar for network maintenance. Another motivation is being an author or coauthor in publications. One way to maintain a network running is social or governmental commitment, after resources expire, studies continue. Conclusion Networks are different due to the social context where they are inserted, however, some characteristics are common to all of them, such as having engaged leaders. For an effective and sustainable network, commitment and motivation in a leader and members are more in need than financial resources. Ideally, to ensure the operation of the network, the institution where the leader is linked should support this network.